A PRELIMINARY STUDY OF INDONESIAN COAL BASINS FOR UNDERGROUND COAL GASIFICATION DEVELOPMENT - Asep Bahtiar Purnama; Miftahul Huda (Indonesian Mining Journal, 2019)
The energy needs in Indonesia are continuing to increase, however, the production of oil and gas declines.This problem can be minimized by developing alternative energy such as underground coal gasification (UCG) by utilizing deep seated coal at 200 to 1.000 m below surface. The objective of this studyis to evaluate coal characteristic in the basins for UCG purpose depends on several coal properties such as its rank (below bituminous), thickness (5m), depth (up to 200m), and ash content plus total moisture (below 60%). Based on coal analysis of 11 coal basins from previous exploration drilling, there were several coal layers in four selected basins to be applied for the UCG project, namely 7 coal layers in South Sumatra Basin, 7 coal layers in Barito Basin, 2 coal layers inAsam-asam Basin and 5 coal layers in Kutai Basin. Based on the SNI No. 5015-2011, the coal resources was calculated and converted into a gas by a simulation procedure. Total UCG coal in South Sumatera Basin is 801 million tons, meanwhile, the Barito Basin has 436 million tons, Asam-asam 136 million tons, and Kutai 289.7 million tons. The total hypothetical syngas is 8.38 TSCF. The UCG facilities in South Sumatra Basin should be designed to produce the syngas as the natural gas within this area is in deficit condition and the basic cost for electricity supply belongs to low situation, however, the UCG plants in Kalimantan should produce electricity as its cost ratio of electricity is high and this area retains surplus natural gas supply.